Costus afer Protects Cardio-, Hepato-, and Reno-Antioxidant Status in Streptozotocin-Intoxicated Wistar Rats - Tchamgoue, Armelle D. (Biomed Res Int, 2018)
Medicinal plants are efficient modulators of oxidative stress associated with diabetes mellitus. This study evaluated the cardio-, reno-, and hepato-antioxidant status of hydroethanolic extract of Costus afer on streptozotocin-intoxicated diabetic rats. Experimental animals were daily administered with hydroethanolic extract of C. afer by oral intubation for eight weeks (60 days), after which the levels of catalase (CAT), superoxide dismutase (SOD), glutathione (GSH), and lipid peroxidation marker (MDA) were evaluated in the heart, liver, and kidney homogenates. Plasma biochemical parameters such as aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), total protein, creatinine, and urea were determined. Meanwhile, parts of the heart, kidneys, and liver were histopathologically examined. Streptozotocin administration induced toxicity in the cardiac, hepatic, and renal tissues by stimulating significant increases (p<0.05) in the levels of CAT and SOD, GSH, and MDA. Similarly, significant increases (P<0.05) in the levels of ALT, AST, urea, and total protein were observed in streptozotocin treated rats, whereas decreases were observed in the levels of ALP, LDH, and creatinine. Following the treatments with C. afer hydroethanolic extract prevented the effect of streptozotocin by maintaining the tissue antioxidant status (CAT, SOD, GSH, and MDA) and the plasma biochemical parameters (AST, ALT, ALP, LDH, creatinine, and urea) towards the normal ranges. The histopathological examination revealed hepatovascular congestion and leucocyte infiltration as well as renovascular congestion, glomerulosclerosis, and tubular clarification in the untreated diabetic control and their absence in the group of animals treated with a high dose of C. afer extract. The findings of the present investigation suggest that C. afer possesses antioxidant activities capable of regulating drug induced tissue damage.